Peningkatan Kapasitas Kader Kesehatan Dalam Upaya Pencegahan Stunting Di Desa Mangki Kecamatan Cempa Kabupaten Pinrang - Sitti Patimah; Idhar Darlis; N Nukman; Andi Nurlinda (Universitas Muhammadiyah Parepare)
The prevalence of stunting that occurred in Pinrang Regency was still very high, amounting to 38.2%. This shows that the health cadres do not comprehensively understand stunting and have never been trained in how to measure the length or height of a toddler. The purpose of this community service activity is to increase the health cadres' knowledge of stunting comprehensively and to detect toddlers at risk of stunting. The method used in this service is counseling and training. Counseling is done with a lecture accompanied by a guidebook for the detection of children under five years of age with stunting risk. For training, cadres were given knowledge of how to measure length and height using video as a demonstration tool. The impact of counseling and stunting detection training for toddlers with stunting was assessed through a pre-test and post-test using a questionnaire. The results of the activity showed that the health care cadres training resulted in an increase in the number of cadres who had known measurement techniques by 87.5%, as well as an increase in the percentage of cadres who knew about stunting by 81.3%. Counseling activities and training provided to health cadres can increase the capacity of Posyandu cadres in understanding stunting and how to detect toddlers at risk of stunting.